Synergistic Effect of Plant Extracts on Endodontic Pathogens Isolated from Teeth with Root Canal Treatment Failure: An In Vitro Study - Suraj Arora; Shahabe Abullais Saquib; Youssef A Algarni; Mohammed Abdul Kader; Irfan Ahmad; Mohammad Y Alshahrani; Priyanka Saluja; Suheel Manzoor Baba; Anshad M. Abdulla; Shashit Shetty Bavabeedu (MDPI AG, 2021)
Background and objectives: This study aimed to evaluate the synergistic antimicrobial activity of extracts obtained from Salvadora persica (Miswak), Commiphora molmol (myrrh) and Azadirachta indica (neem) in combination with commercially available antimicrobial agents: penicillin, tetracycline, ofloxacin and fluconazole on endodontic pathogens such as Enterococcus faecalis, Streptococcus mitis,Actinomyces naeslundii and Candida albicans. Materials and Methods: Microbiological samples from the root canals of the teeth undergoing retreatment were taken using sterile paper points kept at full length in the canal for 30 s. The disc diffusion method was used to check the susceptibility of microbes to the plant extracts and antimicrobials by measuring the diameter of the inhibition zones. Against the microbes, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC)/minimum fungicidal concentration (MFC) of the plant extracts were assessed. The fractional inhibitory concentration index (FICI) was used to estimate the synergistic effect of plant extracts combined with antimicrobials against the resistant endodontic microbes. Results: The findings clearly indicate the effectiveness of all the three plant extracts, Commiphora molmol, Azadirachta indica, Salvadora persica, against all the experimental pathogenic microorganisms except for the ineffectiveness of Azadirachta indica, Salvadora persica against Candidaalbicans. Maximum antimicrobial activity was displayed by Azadirachta indica against Enterococcusfaecalis (MIC = 0.09 ± 1.2 mg/mL, MBC = 0.78 ± 1.25 mg/mL) and the minimum antimicrobial activity was displayed by Commiphora molmol against Actinomyces naeslundii (MIC = 12.5 ± 3.25 mg/mL, MBC = 100 ± 3.75 mg/mL). The best synergy was displayed by Commiphora molmol with fluconazole against Candidaalbicans (FICI = 0.45). Conclusions: The current study delineates the variable antimicrobial activity of plant extracts against the experimental endodontic pathogenic microorganisms. Plant extracts in conjunction with various antimicrobials can be valuable aids in combating relatively resistant endodontic microorganisms that have been the cause of worry in recent years, leading to failure even in treatment procedures following all required protocols.